Histomorphometric and Micro-CT Evaluation of Cerabone and Bio-Oss in Maxillary Sinus Lifting: A Randomized Clinical Trial - Pereira, Rodrigo dos Santos; de Carvalho, Marcus Vinicius Neumann Brandão; Hochuli-Vieira, Eduardo [UNESP]; Statkievicz, Cristian [UNESP]; Pereira Santos, Déborah Laurindo; Augusto Neto, Renato Torres; Pinto, Carolina de Fátima Soares; Bennardo, Francesco; Mourão, Carlos Fernando (MDPI, 2024)
Background and Objectives: The loss of teeth in the posterior maxillary region often leads to significant alveolar bone resorption and maxillary sinus pneumatization, complicating dental implant placement. Maxillary sinus grafting, typically using autogenous bone, is a common solution. However, autogenous bone grafts require additional surgical procedures, leading to increased morbidity. This study aims to compare the efficacy of two xenografts, Bio-Oss and Cerabone, in promoting new bone formation in maxillary sinus grafting through histomorphometric analysis and micro-computed tomography (micro-CT). Materials and Methods: A total of 22 maxillary sinuses (12 right and 10 left) were grafted, with 12 using Cerabone and 10 using Bio-Oss. Six months post-grafting, biopsies were collected for histomorphometric analysis to measure new bone formation, connective tissue, and residual biomaterial. Additionally, micro-CT analysis was performed to assess bone volume fraction, trabecular thickness, number, and separation. Results: Histomorphometric analysis showed that the Cerabone group had a higher average new bone formation (25.94% ± 10.55) compared to the Bio-Oss group (17.29% ± 4.61), with a statistically significant difference (p = 0.02). Micro-CT analysis revealed that the bone volume fraction in the Cerabone group was significantly higher compared to the Bio-Oss group, with significant differences in trabecular thickness (p = 0.02) but not in trabecular number or separation. Conclusions: The study demonstrates that both xenografts are effective in promoting new bone formation in maxillary sinus grafting. However, Cerabone showed superior performance in terms of new bone formation and bone volume fraction, suggesting it may be a more effective option for maxillary sinus augmentation procedures.
Keywords: Bio-Oss; Cerabone; maxillary sinus; xenograft